Gustav Shpet's deep semiotics: A science of understanding signs - Vladimir Feshchenko (Sign Systems Studies, 2015)
The article examines the implicit tradition of deep semiotics in Russia initiated by Gustav Shpet, a Russian philosopher of language. Shpet’s semiotic approach was developed synchronously with the major lines of European and American semiotics (Saussurian and Peircean), but has not been sufficiently known or studied. The recent publication of previously unknown papers by Shpet makes this Russian philosopher an advanced figure on the Russian semiotic scene. Shpet was one of the first Russian scholars to use the term ‘semiotics’, by which he meant a “general ontological study of signs”. Shpet used this term in his work History as a Problem of Logic as early as in 1916. Shpet’s main work on semiotics, the book Language and Sense (1920s), traced back the origins of semiotic thinking and laid the foundations for new semiotics, by which he meant a science of understanding signs. It is here that Shpet spoke of the ontological study of a sign, calling this study semiotics, or else characterics, and raising the issue of the semiotic mind.